2021
DOI: 10.1016/j.eswa.2020.114155
|View full text |Cite
|
Sign up to set email alerts
|

Sentiment analysis and its applications in fighting COVID-19 and infectious diseases: A systematic review

Abstract: Highlights Understanding Sentiment Analysis Role and Opinion Mining In Covid-19 and Other Infectious Diseases. Literature’s Categorization for Sentiment Analysis and Infectious Disease. Academic Challenges and Motivations of Sentiment Analysis with Infectious Diseases. Different Applications for Mitigating Infectious Diseases by Sentiment Analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
185
0
10

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 287 publications
(196 citation statements)
references
References 63 publications
(146 reference statements)
1
185
0
10
Order By: Relevance
“…A recent survey retrieved a few studies that examined the presence of pandemics such as COVID-19 via sentiment analysis [22] , probably because the previous epidemics were smaller. Social media is an important news medium nowadays, studies that help understand people’s behavior could help authorities manage a situation.…”
Section: Related Workmentioning
confidence: 99%
“…A recent survey retrieved a few studies that examined the presence of pandemics such as COVID-19 via sentiment analysis [22] , probably because the previous epidemics were smaller. Social media is an important news medium nowadays, studies that help understand people’s behavior could help authorities manage a situation.…”
Section: Related Workmentioning
confidence: 99%
“…A PRISMA framework is frequently used in the literature [16][17][18][19][20][21][22][23] which is followed as the review methodology of this study. e referenced review studies have considered the following issues in designing their review frameworks: (1) search strategy, (2) inclusion-exclusion criteria, (3) study selection, and (4) data extraction and classification.…”
Section: Review Methodologymentioning
confidence: 99%
“…Sentiment analysis is an extremely important tool to analyze and predict the key events and trends with ongoing time. In this context, Alamoodi et al have shown a great application in fighting against Covid-19 [45]. They aimed to develop a coherent database of all literature on similar medical and pandemic events from the past ten years that has been published with major online research paper databases.…”
Section: Recent Trends In Sentiment Analysismentioning
confidence: 99%